2021
DOI: 10.1002/jsfa.11692
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whole peanut within an energy‐restricted diet on inflammatory and oxidative processes in obese women: a randomized controlled trial

Abstract: BACKGROUND Peanut consumption has little effect on body weight, despite its high energy density and is associated with reduced cardiovascular disease risk. Based on previous research, we hypothesized that the consumption of whole peanut would be associated with greater improvements in body composition, lipid profile, and biomarkers of inflammation and oxidative stress. METHODOLOGY Twenty‐four women with obesity [body mass index (BMI) > 30 kg m−2], 33.1 ± 8.7 years old, were assigned to three groups and consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(47 citation statements)
references
References 55 publications
0
47
0
Order By: Relevance
“…The review includes two papers that reported data from the same study (34,35) ; both papers reported body mass, BMI, fat mass and lean mass, whilst per cent fat mass and per cent lean mass were reported in Alves et al (34) and glycaemic control (glucose, insulin and HOMA-IR) was reported in Moreira Alves et al (35) . Of the eight papers included in this review, one paper reported an intention-to-treat and a compliers analysis (36) , three papers reported only an intention-to-treat analysis (34,37,38) and four papers reported a completers analysis (35,(39)(40)(41) .…”
Section: Study Inclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…The review includes two papers that reported data from the same study (34,35) ; both papers reported body mass, BMI, fat mass and lean mass, whilst per cent fat mass and per cent lean mass were reported in Alves et al (34) and glycaemic control (glucose, insulin and HOMA-IR) was reported in Moreira Alves et al (35) . Of the eight papers included in this review, one paper reported an intention-to-treat and a compliers analysis (36) , three papers reported only an intention-to-treat analysis (34,37,38) and four papers reported a completers analysis (35,(39)(40)(41) .…”
Section: Study Inclusionmentioning
confidence: 99%
“…Study publication dates ranged from 2003 to 2022. Studies were conducted in North America (36)(37)(38)40) , Brazil (35,41,42) and Iran (39) . Across all studies, 676 participants aged between 18 and 79 years were included.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not surprising given that consumption of low energy-dense foods such as fruit juices and sugar-sweetened beverages are associated with higher energy intake and body weight [ [209] , [210] , [211] , [212] ] because they elicit weak energy compensation. In addition, the consumption of high energy-dense foods, such as nuts, does not lead to weight gain [ [213] , [214] , [215] , [216] ] owing to a variety of mechanisms such as their high satiety value, limited energy bioavailability, and potential to increase resting energy expenditure [ 217 ]. Moreover, the primary determinants of dietary energy density, that is, water (0 kcal/g) consumption [ 218 , 219 ], fat (9 kcal/g) consumption [ 220 ], and fiber (1–2 kcal/g) consumption [ 221 , 222 ] have remained relatively stable in the American population while BMI has increased.…”
Section: Introductionmentioning
confidence: 99%
“…The regular consumption of nuts and peanuts has been associated with a reduced risk of developing cardiovascular diseases [ 1 , 2 , 3 ] and diabetes [ 4 , 5 , 6 ], with improvements in the lipid profile, inflammation markers, and preservation of endothelial function [ 7 , 8 , 9 , 10 ]. However, the results of studies evaluating the impact of nut consumption on inflammation are discrepant, as clinical trials have not been able to consistently verify the anti-inflammatory effects found in observational studies [ 8 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%